Navigating fair play in sport by embracing integrity and ethics - Krambia-Kapardis, Maria (My University, 2023)
Sport is a fundamental pillar of civil society. A large proportion of the world’s population enjoys participating in sport. It is worth acknowledging that sport has strong educational and formation values as it contributes to teamwork, advancing one’s leadership skills, healthy living, friendship, solidarity and many more. In addition to the positive contributions to society and individuals who participate in sport there are strong economic benefits. Researchers have stated that sport on average contributes 2.5- 3.5% to the GDP of a country while the sports’ industry has been estimated to be worth $US1.3 trillion. At the same time, it is estimated that in 2023 the annual worldwide gross gambling in sport yield will be higher than $400 billion reached in 2015, while match-fixers hauled in profits about $177million in 2021. Thus, sports have not only multifaced contributions to the wellbeing of individuals and society but have a direct impact on the economy of a country. Therefore, it is in the vested interest of society, politicians, educators, researchers and businesses to ensure the sustainability of sport and the wellness of the stakeholders. It has been advocated that sports have reached the fifth evolutionary trend that of Criminalization. Recent statistics from SportRadar, FIFA and others do highlight the hot potato for the 21st century by discussing match fixing and the gambling market. They have discussed that not only first league teams are affected but players themselves may be addicted to gambling thus they too may be involved in match fixing. Thus, the issue of unethical and illegal behaviour is having bigger repercussions and affects younger players or even potential players not to mention the entire sports’ industry. The author of the current paper discusses the findings of a study carried out in Cyprus of football players, team management, referees and offers policy implications on how to best address match-fixing, gambling and other corruption or illegal behaviour through the implementation of a holistic prevention model. Ethics and Integrity are an integral part of the model in an effort to not only address the issue in the short time but to also ensure the next generation of stakeholders have moral fibre and moral character to implement ‘fair play’.
Keywords: Sports corruption; Match fixing; Integrity